An exploratory study of the effectiveness of the “Program Pembangunan Rakyat Khas” (PPRK) of SEDC in the Kuching district since its implementation in 1993 / Iswandy Shafi-ee - Shafi-ee, Iswandy (2002)
The government and the statutory body has tried their best to eradicate poverty among the people such that now in 2002 less than 10% Malaysian are poor compare to over 50% in 1970. Therefore this exploratory take place to measure the effectiveness of PPRK programme that has been implemented by SEDC to encounter this problem. The exploratory study reported in this research was based on a survey of the PPRK participants located in Kuching District, supported by data from Sarawak Economic Development Corporation (SEDC), Rural Entrepreneur Development Unit (RENDU), as well as personal observations, questionnaires, and interviews with relevant authorities and personnel. The objective of the PPRK programme are to provide support to poor household to enable them to move out of poverty and the programme is to be extended to all PPRK participants in the state. This study also presents the economic situation and the extent of the poverty eradication among the PPRK participants in Kuching District. This study also examines the implications and the efforts taken by the SEDC in attainining the distributional objective for the PPRK participants in coherent to reduce poverty among the Bumiputera. Due to no formal education among the PPRK participants has not helped them to get out of the worlds of absolute poverty.